Beautiful Serbia - Holger Bonin; Ulf Rinne (Institute for the Study of Labor (IZA), 2006)
The paper studies the causal impact of participation in an active labor market program - the 'Beautiful Serbia' program providing training and temporary work in the construction sector in Serbia and Montenegro - on measures of subjective well-being approximating individual welfare. According to our estimates, the positive impact of this particular program appears much stronger judged by subjective well-being than judged by the immediate labor market effect.
urn:nbn:de:101:1-2008042976
Keywords: 330